Children’s right to health : a contextual analysis of the influences of Jehovah’s Witness-guardians’ consent to life-saving medical procedures for children in Zambia - Akintayo, Akinola (University of Pretoria, 2021)
Mini Dissertation (LLM)--University of Pretoria, 2021.